A Metallo- Silsesquioxane Synthesized from Cu (II) via a Cyanide Fe (III) Bridge: Synthesis and Application as an Electrochemical Sensor - da Silva Carvalho, Victor Aparecido [UNESP]; Peixoto, Murilo Santos [UNESP]; dos Santos Felipe, Alexsandro [UNESP]; Sales, Abner Santos Baroni [UNESP]; Masteralo, Valmor Roberto; Dias Filho, Newton Luiz [UNESP]; do Carmo, Devaney Ribeiro [UNESP] (Wiley, 2024)
A new metallohybrid silsesquioxane (S) was synthesized herein from copper and ferricyanide via a cyanide bridge to produce a new electroactive hybrid material (SCuH), which was then characterized by spectroscopic and microscopic techniques and cyclic voltammetry. The voltammetric behavior of SCuH employing a graphite paste electrode indicates a well-defined redox couple with formal potential Eθ′=0.76±0.01 V. The electrode exhibited high sensitivity to nitrite and was successfully tested for nitrite detection. The linearity of the analytical curve was 2.0×10−4 mol L−1 − 1.0×10−3 mol L−1, with a limit of detection of 2.65×10−5 mol L−1, and sensitivity amperometric value of 57.63 mA/mol L−1. These findings suggest that this material displays exceptional potential for application in electrochemical sensors designed for nitrite detection.
Keywords: Copper hexacyanoferrate (III); Electrochemical sensor; Hybrid materials; Nitrite; Silsesquioxane; Voltammetry